2022
DOI: 10.1177/0160323x221097711
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Local Economic Development in Light of COVID-19

Abstract: The COVID-19 pandemic pressured local governments to employ creative and untested economic development strategies to stabilize private businesses. To explore how the uncertainty of the pandemic impacted the priorities and strategies of economic development officials, we surveyed officials about their initial economic development response to the pandemic coupled with subsequent in-depth interviews in the Cincinnati metropolitan region. Our analysis suggests that local officials did not drastically alter their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Economic development is a traditional local government priority, and over 50% of cities indicate that they are doubling down on this as part of their COVID response. This comports with findings from other recent studies, which also observed local governments adjusting their mix of economic development strategies and increasing emphasis on collaboration to navigate the uncertain economic conditions ( Johnson et al 2022 ).…”
Section: Resultssupporting
confidence: 88%
“…Economic development is a traditional local government priority, and over 50% of cities indicate that they are doubling down on this as part of their COVID response. This comports with findings from other recent studies, which also observed local governments adjusting their mix of economic development strategies and increasing emphasis on collaboration to navigate the uncertain economic conditions ( Johnson et al 2022 ).…”
Section: Resultssupporting
confidence: 88%
“…Their amount also depends on the municipality's economic, social, and political development Lewis and Oosterman (2011). argue that the implementation of investment projects by local government units (LGUs) affects the strengthening of their investment activity, which is important for any country, as it positively affects its development.The COVID-19 pandemic has forced LGUs to use creative and untested economic development strategies(Johnson et al, 2022). Afonso (2021) stressed the importance of understanding how government agencies were responding to the challenges of the COVID-19 pandemic and how municipalities used their economic development tools to combat the crisis.…”
mentioning
confidence: 99%
“…The model has been broadly used in empirical studies to forecast the economic impacts of tourism. To summarize how a project impacts at community or regional level, conforming to Johnson (1999) better using Input-Output analysis instead of the other models. Tourism-related information, formed in data & model, is required to influence both tourism activities as well as their relationship with local and regional economic activities.…”
Section: Chapter 3 Methodologymentioning
confidence: 99%